PENGARUH OLAHRAGA INTENSITAS SEDANG TERHADAP KUALITAS TIDUR LANSIA DI PIMPINAN RANTING AISYIYAH CABANG MELATI PADA TAHUN 2018 - NABILA HANA SYAQILA; GUSBAKTI RUSIP; AMELIA EKA DAMAYANTI; ROBITAH ASFUR (JURNAL ILMIAH SIMANTEK, 2020)
Increasing the elderly population globally is a challenge and also an opportunity in all countries. This increase will have apositive impact if the elderly are in a healthy, productive and independent situation. WHO (World Health Organization) statedthat the elderly population in Indonesia in the next two years, in 2020 will reach more than 28 million people, placingIndonesia as the country with the largest elderly population in the world. Healthy elderly refers to the active concept of agingstated by WHO. According to WHO, active aging is the process of developing and maintaining the ability of the elderlyincluding basic needs for the elderly, social interaction and play a role in society, contribute and be able to build and maintainsocial relations. It can be said that a healthy elderly person is a person who has a good quality of life. One indicator of goodquality of life is the quality of sleep. Based on the background the researcher have described above, researcher is interestedknowing the effect of moderate intensity exercise on the quality of elderly sleep at the Pimpinan Ranting Aisyiyah CabangMelati, Medan 2018. This study aims to know the effect of moderate intensity exercise towards quality of sleep in elderly atthe Pimpinan Ranting Aisyiyah Cabang Melati, Medan 2018. This study is experimental using quasi experiment pre-test posttestcontrol group design. Data are collected by PSQI quesionairre. The results of the study showed that there was an effectof moderate intensity exercise towards quality of sleep in elderly at Pimpinan Ranting Aisyiyah Cabang Melati, Medan.Using Wilcoxon Test obtained the p value = 0.001 in the group of respondents who were given the intervention. There is aneffect of moderate intensity exercise towards quality of sleep in elderly at Pimpinan Ranting Aisyiyah Cabang Melati, Medan.